Penggunaan media gambar dalam meningkatkan aktivitas dan hasil belajar IPA pada materi rangka dan pemeliharaannya siswa kelas IV MIN 9 Aceh Barat Daya - Muzzalifah, Muzzalifah (Universitas Serambi Mekkah, 2020)
The purpose of this study is to improve the activities and learning outcomes of science in the framework material and its maintenance through the use of image media. The learning method used in this study is the image media method. The subjects of this study were students in grade IV MIN 9 Southwest Aceh. The number of students is 14 students with a total of 7 male students and 7 female students. This re-search was conducted in the 2017/2018 Academic Year within a period of 3 months, from September to November 2017 in Odd Semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. In each cycle consists of plan-ning, implementation, observation and reflection. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Ob-servation data is done by looking at student activities in the learning process. Data were analyzed by means of percentage statistics. The results showed that an increase in student learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Com-pleteness of student learning outcomes has increased from 42.85% in pre-study increased to 64.28% in the first cycle and increased to 85.71% in the second cycle. The application of the use of image media can increase the activities and learning outcomes of science in the framework material and the mainte-nance of fourth grade students MIN 9 Aceh Barat Daya 2017/2018 Academic Year.